If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + -3n = 10 Solving m + -3n = 10 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3n' to each side of the equation. m + -3n + 3n = 10 + 3n Combine like terms: -3n + 3n = 0 m + 0 = 10 + 3n m = 10 + 3n Simplifying m = 10 + 3n
| 5x-12=6x-8 | | (103-x)+(6x-7)=2x | | 3y^3(2y+3)(y-5)= | | 3x-7=9-2x | | (4x+8)+(2x+3)=51 | | 7a^2x^2+2ax-4=0 | | 7a^2x^2+2ax=4 | | 4.5(4x-12)=144 | | 22=12+4t-5t | | 3+(3+y)= | | x+5=25+6x | | (4x+3)(2y-1)= | | 4.65x-4.79=-6.84 | | 3y=5x+6 | | 4x+5y=-2 | | (5-3x)(4+x)= | | 39.21+2.65=42.03 | | 3(2x-5)-5x=15 | | -10g+4g+8=14 | | (6-5m)(2+3m)= | | 7(-1+2x)=-21 | | -2(v-y)+5+(-6y-2v)= | | -5y+1=-13 | | 9a-5=3a+5 | | 6x^2-x-6=0 | | (5a+1)(2a+7)= | | 39-3x-3=7x | | 6x^2+x-6=0 | | 8x^3+10x-3=0 | | 2x+3x-5y-3y= | | -3z-4=10 | | -x=8y+5 |